Cities of power : the urban, the national, the popular, the global / Göran Therborn. - Therborn, Göran, 1941- (Verso, 2017)
In this survey of urban politics, leading sociologist Göran Therborn looks at what makes a metropolis. Through a historical lens and a global perspective, he questions received assumptions about the source of urban power and how it manifests itself. He looks at the way that architecture and social movements have had their impact on the way cities work. He explores what makes a 'global city'. And he argues that, at a time when they seem to be moving apart, there is a strong link between the city and the nation state.